2005
DOI: 10.1152/ajpgi.00048.2004
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated intestinal transit in inbred mice with an increased number of interstitial cells of Cajal

Abstract: The interstitial cells of Cajal (ICC) play an important role in coordinating intestinal motility, and structural alterations in ICC are found in several human digestive diseases. Mouse models with defects in ICC allow a better understanding of their functions. We investigated the pattern of intestinal motility and the distribution of ICC in the PRM/Alf inbred mouse strain, characterized by a selective intestinal lengthening. In PRM/Alf mice, the digestive transit time, evaluated by using thermophilic Bacillus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 41 publications
1
26
0
2
Order By: Relevance
“…Intestinal crypt depths in SIHUMI-PRM/Alf mice were similar to those previously reported for conventional PRM/Alf mice, 15 suggesting that this parameter was not influenced by the type of microbiota. However, the intestinal wall was thicker in SIHUMI-associated PRM/Alf mice than in conventional PRM/Alf mice.…”
Section: Discussionsupporting
confidence: 85%
“…Intestinal crypt depths in SIHUMI-PRM/Alf mice were similar to those previously reported for conventional PRM/Alf mice, 15 suggesting that this parameter was not influenced by the type of microbiota. However, the intestinal wall was thicker in SIHUMI-associated PRM/Alf mice than in conventional PRM/Alf mice.…”
Section: Discussionsupporting
confidence: 85%
“…5B). The results from the 24-h time point also serve to exclude the possibility of contamination of the SI and colon tissue samples by extracellular BaP from the intestinal tract, given the reported transit time for foods through the gastrointestinal tract: ϳ15 h in rats (DeSesso and Jacobson, 2001) and ϳ10 to 11 h in mice (Bellier et al, 2005). Thus, not only can the loss of intestinal P450 activity lead to higher circulating BaP levels but also it can cause significant increases in the tissue burden of the toxicant in the gut and various extra-gut target organs, in mice exposed to BaP through oral ingestion.…”
Section: Role Of Small-intestinal P450s In Reducing Bapmentioning
confidence: 99%
“…It was also found that the number of gastric ICCs in the EA group was greater than that in the model group. It has been suggested that the acceleration of intestinal transition may increase the numbers of ICCs (23). The pathological damage to the ICCs, as well as the nerve endings between ICCs and SMCs, was less than that in the model group, and the structures were more distinct and tightly connected.…”
Section: Discussionmentioning
confidence: 97%